2002
DOI: 10.1038/sj.bjp.0704957
|View full text |Cite
|
Sign up to set email alerts
|

The novel antagonist 3‐CBW discriminates between kainate receptors expressed on neonatal rat motoneurones and those on dorsal root C‐fibres

Abstract: 1 The natural product willardiine is a selective AMPA receptor agonist. We report that an N 3 -substituted analogue of willardiine, (S)-3-(4-carboxybenzyl)willardiine (3-CBW), antagonizes AMPA and kainate receptors expressed on motoneurones and dorsal root C-®bres, respectively. 2 Reduction of the fast component of the dorsal root-evoked ventral root potential (fDR-VRP) has been used as a novel method to compare AMPA receptor antagonists. 3-CBW, NBQX and GYKI53655 depressed the fDR-VRP with IC 50 values of 10.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 37 publications
1
43
0
Order By: Relevance
“…To compare the antagonists for activity at AMPA receptors, their ability to depress the fast component of the dorsal root‐evoked ventral root potential (fDR‐VRP) in the neonatal rat hemisected spinal cord preparation was measured. As reported previously, the fDR‐VRP has been shown to be evoked by the stimulation of AMPA receptors and can therefore be used as a convenient method to compare AMPA receptor antagonists using native receptors (More et al ., 2002b).…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…To compare the antagonists for activity at AMPA receptors, their ability to depress the fast component of the dorsal root‐evoked ventral root potential (fDR‐VRP) in the neonatal rat hemisected spinal cord preparation was measured. As reported previously, the fDR‐VRP has been shown to be evoked by the stimulation of AMPA receptors and can therefore be used as a convenient method to compare AMPA receptor antagonists using native receptors (More et al ., 2002b).…”
Section: Introductionmentioning
confidence: 83%
“…A number of studies have demonstrated the conversion of glutamate receptor agonists into antagonists by extending the chain length between the α ‐carboxylic acid and the terminal acidic group (Davies et al ., 1982; Krogsgaard‐Larsen et al ., 1991; Madsen et al ., 1996; Jane et al ., 2000). We recently demonstrated that the agonist willardiine could be converted into an antagonist of AMPA and kainate receptors by increasing the interacidic group chain length when it was shown that 3‐CBW (( S )‐3‐(4‐carboxybenzyl)willardiine, UBP282) is an antagonist of AMPA receptors on motor neurones and kainate receptors on dorsal root C‐fibres (More et al ., 2002a, b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prototypic GluK1-selective antagonists, such as LY382884 (O'Neill et al, 1998) have low micromolar potency. We therefore developed a series of KAR antagonists based on the structure of the AMPA receptor agonist willardiine (More et al, 2002; More et al, 2003). Over the past few years, a combination of structure-activity relationship studies and homology models (More et al, 2004; Dolman et al, 2005; Dolman et al, 2006) have been used to create novel compounds that show a marked selectivity for GluK1 with potencies ranging from micromolar (UBP296, UBP302 and UBP304) to nanomolar (UBP310).…”
Section: Introductionmentioning
confidence: 99%
“…Drugs are being developed that specifically target glutamate receptor subunits. (RS)-α-amino-3-hydroxy-5-tertbutyl-4-isoxazolepropionic acid (ATPA) is a specific agonist of GluR5-containing kainate receptors [152]; (RS)-2-amino-3-(4-chloro-3-hydroxy-5-isoxazolyl) propionic acid (CI-HIBO) is the most subtype selective agonist reported to date on AMPA GluR1/2 subunits [153]; 4-(2-(phenylsulfonylamino)ethylthio)-2,6-difluorophenoxyacetamide (PEPA) is a highly specific floppreferring allosteric modulator of AMPA receptor desensitisation [154]; and (S)-3-(4-carboxybenzyl)willardiine (3-CBW) discriminates between kainate receptors expressed on neonatal rat motor neurons and those on dorsal root Cfibres [155]. The development of drugs that target specific receptor subunits could allow more subtle effects on function after spinal lesions.…”
Section: Ionotropic Receptorsmentioning
confidence: 99%